1979
DOI: 10.2134/agronj1979.00021962007100020023x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Quality of Bermudagrass and Orchardgrass‐Ladino Clover Pastures for Beef Steers1

Abstract: Bermudagrass (Cynodon dactylon (L.) Pers.) has high potential summer forage production and can help fill the gap in foragebeef production systems during late summer. The productivity and quality of ‘Midland’ grown at four levels of N fertilization (0, 112, 224, 448 kg.ha) as forage systems for grazing beef steers were compared to those of common bermudagrass (C. dactylon var. dactylon) fertilized with 112 kg N/ha and of a mixture of orchardgrass (Dactylis glomerata L) and ladino clover (Trifolium repens L.) (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…We found good yields throughout its entire growing period, from late spring to early summer. This species reached reasonable average yields even when no l~ertilizer N was supplied, but applied N significantly increased the yield of leaves and stems of C. dactylon compared to plants without N supply, as has been also reported by several authors (Decker et al, 1971;Fribourg et al, 1979;Mathias et al, 1978). In other localities it has been shown that the yield of bermudagrass increased linearly with fertiliser rates up to at least 900 kg of N ha -~.…”
Section: Discussionsupporting
confidence: 80%
“…We found good yields throughout its entire growing period, from late spring to early summer. This species reached reasonable average yields even when no l~ertilizer N was supplied, but applied N significantly increased the yield of leaves and stems of C. dactylon compared to plants without N supply, as has been also reported by several authors (Decker et al, 1971;Fribourg et al, 1979;Mathias et al, 1978). In other localities it has been shown that the yield of bermudagrass increased linearly with fertiliser rates up to at least 900 kg of N ha -~.…”
Section: Discussionsupporting
confidence: 80%
“…Grazing systems using forage legumes increase animal production (Fribourg et al, 1979; Jung et al, 1985; Rayburn et al, 1980; Stricker et al, 1979), and pastures with legumes have greater crude protein content, digestibility, and mineral composition for livestock diets, resulting in greater forage intake and animal performance (Marten, 1985). Kroth et al (1982) reported the nitrogen (N) benefits from birdsfoot trefoil ( Lotus corniculatus L.) and alfalfa ( Medicago sativa L.), producing 115 and 200 kg N ha −1 , respectively, annually.…”
mentioning
confidence: 99%
“…Forage production, animal performance, and pasture productivity from orchardgrass + clover, fescue + legumes, and Midland + fescue at 25 em + N were greater than those measured earlier in the region (4,7,10). This increased performance of forage plants and animals may have been due to more favorable climatic conditions, longer grazing seasons, or better management of animals and pastures.…”
Section: General Discussion and Management Implicationsmentioning
confidence: 73%
“…is well adapted to the mid-southeastern USA (3), responds well to N fertilization (2), overseedings of legumes, and to combinations of the two practices ( 1 0). Midland grows well in spring and summer and fills the summer production gap in beef pasture systems utilizing cool-season species ( 4 ). Pas-676 AGRONOMY JOURNAL, VOL.…”
mentioning
confidence: 99%
See 1 more Smart Citation